The best start: supporting, happy childhoods - Hayes, A; Baxter, Jennifer; Gray, M (My University, 2010)
To support the 2010 National Families Week, the Australian Institute of Family Studies has prepared this Facts Sheet about the role that families and communities play in giving children the best possible start to life. Drawing upon data from Growing Up in Australia: The Longitudinal Study of Australian Children, this facts sheet presents key findings on the health and happiness of children from birth to middle childhood, including general health and obesity; parents enjoying time with their children; children enjoying time with their parents after divorce or separation; shared activities with parents; perceived neighbourhood safety and characteristics; and children's self-reported happiness, in general and at school.
Fact Sheet for 2010 National Families Week
Keywords: Child Development; Childhood and child development; Child Development; Childhood and child development